ISSUES OF ENSURING CHILDREN'S AND MINORS' RIGHTS TO WORK - Eshankulov Bunyodjon Makhamadalievich (Scholar Express Journals, 2024)
This scientific article is devoted to the issues of ensuring the rights of children and minors to work, and the author tried to develop proposals for the improvement of international standards and norms, as well as national legislation, in the protection of the rights of minors to work. As the relevance of the topic, the fact that children under 10 years of age are involved in the most difficult forms of labor in today's world, despite the fact that international conventions have been ratified in these countries, the legal requirements are not being followed, the economic and social factors of this have been touched upon. Also, new mechanisms aimed at ensuring the rights of children and minors to work, procedures for their practical application and issues of their improvement have been included in the national legal system.
Keywords: Labor; forced labor; child; transporting